Keberlanjutan Usaha Kuliner: Analisis Tantangan dan Strategi Pengembangan - Muhammad Haikal Faran Fajri; Nabil Naufal Zaki; Randy Arista Pratama (Universitas Muhammadiyah Surabaya, 2024)
Abstract This research employs a qualitative approach to analyze the challenges and development strategies of Rumah Makan Riski Puti Bungsu in maintaining its business sustainability. The study aims to understand the challenges and development strategies of Rumah Makan Riski Puti Bungsu. The findings indicate that menu innovation, quality service, social media promotion, and technology utilization are key to success. The main challenges include intense competition, fluctuating raw material prices, and changing consumer preferences. Suggestions to overcome these challenges include menu diversification, improvement in service quality, and digital marketing. These findings offer valuable guidance for culinary business owners in addressing challenges and sustaining their businesses in an increasingly competitive era. Keywords: Business Sustainability, Development Strategy, MSMEs, Consumer Preferences